Implementation strategies for the first licensed dengue vaccine: A meeting report. Issue 34 (9th August 2021) - Fongwen, Noah; Delrieu, Isabelle; Ham, Leong Hoe; Gubler, Duane J.; Durbin, Anna; Ooi, Eng-Eong; Peeling, Rosanna W.; Flasche, Stefan; Hartigan-Go, Kenneth; Clifford, Sam; Martinez, Carlos Torres; de Lamballerie, Xavier; et al.
Abstract: Dengue vaccination would enhance the control of dengue, one of the most frequent vector-borne viral diseases globally. CYD-TDV is the first dengue vaccine to be licensed, but global uptake has been hampered due to its use being limited to seropositive persons aged 9 years and above, and the need for a 3-dose schedule. The Partnership for Dengue Control (PDC) organized a meeting with key opinion leaders and stakeholders to deliberate on implementation strategies for the use of CYD-TDV. New data have emerged that support the shortening of the primary schedule from a 3 to 2 dose schedule, extending the age range below 9 to 6 years of age, and expanding the indication from endemic populations to also include travelers to endemic areas. Cost-effectiveness may improve with the modified 2-dose regimen and with multiple testing. Strategies to implement a dengue vaccination program have been developed, in particular school-based strategies. A range of delivery scenarios can then be considered, using various settings for each step of the intervention. However, several challenges remain, including communication about limiting the use of this vaccine to seropositive individuals only. Affordability will vary from country to country, as will government commitment and community acceptance. Well-tailored communication strategies that target key stakeholders are expected to make up a significant part of any future dengue vaccination program.